2015
DOI: 10.1038/nature15641
|View full text |Cite
|
Sign up to set email alerts
|

Electrical signalling goes bacterial

Abstract: WAT and mediate leptin-stimulated lipolysis is not surprising. However, Zeng and colleagues' study fills a gap in our understanding of precisely how organisms respond to an abundance of leptin. Their work also specifically demonstrates that sympathetic neurons projecting to WAT are a central trigger for leptin-mediated lipolysis. Of course, questions arise from these findings. Leptin is thought to signal through several brain areas 11 , but it remains unclear which neuronal networks sense increased blood lepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Gut bacteria can influence the excitability and electrophysiological properties of enteric neurons through ion-channel-related actions [43,44]. Furthermore, it has been demonstrated that bacteria communicate with each other via some of the same mechanisms and algorithms used by neurons in the brain (ion-channel-mediated electrical and chemical signaling, which underlie computation) [40,[45][46][47][48][49][50][51][52], performing cognitive tasks both as individual bacterial cells and as colonial super-organisms [53,54]. The rich behavioral and ion-channel-or bioelectricity-related repertoire of these two systems suggests that they, and the communication interface between them (which is increasingly being recognized as a crucial part of human physiology [41,55,56]), can be exploited to tackle fundamental questions of the bidirectional communication between neurons and bacteria.…”
Section: Do the Gut Microbiota And Brain Talk To Each Other?mentioning
confidence: 99%
“…Gut bacteria can influence the excitability and electrophysiological properties of enteric neurons through ion-channel-related actions [43,44]. Furthermore, it has been demonstrated that bacteria communicate with each other via some of the same mechanisms and algorithms used by neurons in the brain (ion-channel-mediated electrical and chemical signaling, which underlie computation) [40,[45][46][47][48][49][50][51][52], performing cognitive tasks both as individual bacterial cells and as colonial super-organisms [53,54]. The rich behavioral and ion-channel-or bioelectricity-related repertoire of these two systems suggests that they, and the communication interface between them (which is increasingly being recognized as a crucial part of human physiology [41,55,56]), can be exploited to tackle fundamental questions of the bidirectional communication between neurons and bacteria.…”
Section: Do the Gut Microbiota And Brain Talk To Each Other?mentioning
confidence: 99%
“…Already simple cells of bacteria enjoy sensory systems feeding into cognitive-behavioral circuits and showing many other neural features ( Miller and Koshland, 1977 ; Koshland, 1980 ; Lyon, 2015 ). Electrical long-distance signaling and information exchange via spatially propagating waves of potassium is synchronizing bacterial biofilms ( Beagle and Lockless, 2015 ; Nunes-Alves, 2015 ; Prindle et al, 2015 ). Integrated bacteria within the biofilm community appear to act as some kind of ‘microbial brain’.…”
Section: Neurons: Their Powers Evolutionary History and Beyondmentioning
confidence: 99%
“…To coordinate their intense social acitivity, research carried out in the last twenty years strongly suggests that bacteria typically engage in cellto-cell communication (Kolter and Greenberg, 2006;Mukherjee and Bassler, 2019). Increasing evidence points at the existence of intra-species, interspecies (Ley et al, 2008) and inter-kingdom communication (Hughes and Sperandio, 2008;Ismail et al, 2016), as well as dierent kinds of signaling systems including a form of electrical signals (Prindle et al 2015;Beagle and Lockless, 2015).…”
Section: Bacterial Signalingmentioning
confidence: 99%